Dry eye disease severity and impact on quality of life in type II diabetes mellitus - Zhmud, Tetiana; Malachkova, Natalia; Rejdak, Robert; Costagliola, Ciro; Concilio, Marina; Drozhzhyna, Galyna; Toro Mario, Damiano; Veretelnyk, Svitlana (Frontiers in Medicine, 2023)
Aim: To assess the severity of dry eye disease (DED) in humans, its impact on quality of life (QoL) and to grade the damage incurred by the anterior ocular surface in patients diagnosed with type 2 diabetes mellitus(T2DM). Patients and Methods: Forty-six patients (mean age ± SD= 63.8 ± 6.7 years) diagnosed with T2DM were enrolled in the experimental group and 26 healthy individuals constituted the control group (67.9 ± 8.9 years). The diagnosis and gradation of DED were conducted in accordance with the International Task Force severity grading scheme. Disease-specific questionnaires were used to obtain the Ocular Surface Disease Index (OSDI) and assess the negative effects of the disease on the patient’s QoL. The severity of conjunctival redness and corneal/conjunctival staining was assessed by Efron and Oxford scales, respectively. Results: According to OSDI scores, the entire experimental group presented symptoms of DED: 54.4% were diagnosed with mild DED and 46.6% with moderately severe DED. No cases of severe DED were diagnosed in either the experimental or control group. In the control group, 57.7% of individuals did not have the disease. A significant difference between the experimental and control groups was recorded for both OSDI scores (p<0.01) and health-related QoL (p˂0.01). It was observed that keratopathy influenced the mean OSDI values of patients. The mean OSDI value was 25.14 ± 3 in the experimental group diagnosed with keratopathy, 19.3 ± 3.5 in the subgroup with no indications of corneal injury (p=0.000002), and 13.0 ± 3.0 in the control group (p<0.000002). Based on the DEWS scheme, a grade I severity level was observed in 46% of control subjects and 33% of patients diagnosed with T2DM (p=0.4915); grades II and III were detected in the bulk of the experimental group (p=0.0051; p=0.1707). None of the subjects in the control or experimental groups manifested grade IV severity of DED. Conclusion: In comparison to healthy adults, DED adversely impacts the QoL of type 2 DM patients, regardless of the disease’s association with keratopathy.